Role and Impact of World Bank Structural Adjustment Programs in Developing Countries - Ahlam Nassar Omar Saeed (Humán Innovációs Szemle)
This paper aims to analyze the World Bank's Structural Adjustment Programs (SAPs) and their impact on Jordan's development trajectory. Jordan serves as a representative case study in the Middle East. The main aim is to examine the dual nature of SAPs as possible catalysts or obstacles to development, closely examining their economic, social, and political impacts. The paper utilizes a combination of qualitative methods to assess the impact of SAP-related changes on economic indicators and analyze the social consequences on Jordanian society. This study is based on a theoretical framework that incorporates multiple disciplines. It explores economic theories that address market imbalances, the consequences of poor governance, and the controversial components of neoliberalism. The study focuses on market liberalization, privatization, and fiscal austerity in Structural Adjustment Programs (SAPs) by critically examining the principles of the Washington Consensus and its neoliberal origins. The results suggest that although SAPs have aimed to boost productivity and integrate Jordan into the global economy, the outcomes have been inconsistent. The analysis reveals that policies implemented by SAPs have resulted in a temporary economic improvement, as well as causing deeper social inequalities, weakening local industries, and generating widespread discontent among the population. It concludes by offering several policy recommendations aimed at maximizing the advantages of SAPs while minimizing their negative consequences. The study emphasizes the importance of policy reforms that take into account Jordan's specific circumstances. It highlights the need to reconsider SAP strategies to better match the socioeconomic conditions of developing countries.